Perancangan dan Simulasi Tata Letak Pabrik Untuk Mengoptimalkan Biaya Material Handling Dengan Menggunakan Algoritma Craft dan Activity Relationship Chart pada Industri Kerajinan Bambu - Nabila Noor Qisthani; Ichsanny Aprilia Sitorus; Heny Agustina Lusianti (JIE Scientific Journal on Research and Application of Industrial System, 2021)
CV. XYZ is one of small and medium entrepreneurship producing a wide range of bamboo handicrafts such as chairs, tables, partitions, etc. The company wants to increase profit by saving on production costs and optimizing transport material handling distances between the production process directly related to the layout of the factory. In research conducted in CV XYZ, there is an inefficient layout. This is indicated by irregular material flows, storage of the residual material production and a lot of material movement between operations. Type of layout used is process layout design, with the objective to minimize the total movement moment. The algorithm used is the CRAFT algorithm that requires data of transfer materials cost (multiplication of the distance with the frequency of movement). Besides methods used in this research is qualitative method that ' s using map relations activity diagram relations activity. Beside that simulation is performed to compare the existing layout with the proposed layout. Based on the research that has been done, the layout of the proposed methods can reduce the CRAFT movement of the moment of total material to 16.25% with yields as much as 21 Product Family Chair in one month while the layout of the proposed use of the ARC produces as many as 20 products only.